Influence of ethnicity on acceptability of method of blood pressure monitoring: a cross-sectional study in primary care - Wood, S; Greenfield, S; Sayeed Haque, M; Martin, U; Gill, P; Mant, J; Mohammed, M; Heer, G; Johal, A; Kaur, R; Schwartz, C; McManus, R (Royal College of General Practitioners, 2016)
Background: Ambulatory and/or home monitoring are recommended in the UK and the US for the diagnosis of hypertension but little is known about their acceptability. Aim: To determine the acceptability of different methods of measuring blood pressure to people from different minority ethnic groups. Design and setting: Cross-sectional study with focus groups in primary care in the West Midlands. Method: People of different ethnicities with and without hypertension were assessed for acceptability of clinic, home, and ambulatory blood pressure measurement using completion rate, questionnaire, and focus groups. Results: A total of 770 participants were included, who were white British (n = 300), South Asian (n = 241), and African Caribbean (n = 229). White British participants had significantly higher successful completion rates across all monitoring modalities compared with the other ethnic groups, especially for ambulatory monitoring: white British (n = 277, 92% [95% confidence interval [CI] = 89% to 95%]) versus South Asian (n = 171, 71% [95% CI = 65% to 76%], P<0.001) and African Caribbean (n = 188, 82% [95% CI = 77% to 87%], P<0.001), respectively. There were significantly lower acceptability scores for minority ethnic participants across all monitoring methods compared with white British participants. Focus group results highlighted self-monitoring as most acceptable and ambulatory monitoring least acceptable without consistent differences by ethnicity. Clinic monitoring was seen as inconvenient and anxiety provoking but with the advantage of immediate professional input. Conclusion: Reduced acceptability and completion rates among minority ethnic groups raise important questions for the implementation and interpretation of blood pressure monitoring. Selection of method of blood pressure monitoring should take into account clinical need, patient preference, and potential cultural barriers to monitoring.